Motivation And Perception To Support Purchasing Decisions In “Cafe & Resto Benteng Buah Naga”, Banyuwangi, East Java, Indonesia - Yhanis Andita Sari; Gumoyo Mumpuni; Dyah Erni Widyastuti (Universitas Muhammadiyah Malang, 2021)
“Café & Resto Benteng Buah Naga” (“Dragon Fruit Fortress Café & Resto”) presents an innovation based on dragon fruit products, then the initial perception will determine consumer's motivation to visit the place. The research purposed to determine the consumer’s characteristics and to state the influence of motivation and perception on purchasing decisions. The research was conducted at “Café & Resto Benteng Buah Naga” in Banyuwangi Regency, East Java Province. The sampling method was accidental sampling with 100 respondents. The data analysis used was path analysis. The results show that the majority of respondents were women (68%) with the status as a student who has an income maximum IDR 1,000,000. The motivation variable partially affects the purchase decision, as it obtains a sig value of 0.036 which means < 0.05. Variable perception obtains a sig value of 0.000 which means < 0.05, partially significant effect also on the purchase decision. It could be concluded that the consumer’s motivation and perception influence purchasing decisions at “Café & Resto Benteng Buah Naga”. The advice given is that “Café & Resto Benteng Buah Naga” continues to develop more dragon fruit-based product variants and become their special menu at the restaurant.